Building Behavior and Performance Citizenship: Perceived Organizational Support and Competence (Case Study at SPMI Private University In West Sumatra) - Ridwan, Muhammad; Mulyani, Sitti Rizki; Ali, Hapzi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the effect of perceived organizational support and competence on organizational citizenship behavior (OCB) and performance, and also analyze OCB on employee performance at SPMI Private University in West Sumatra. The population is all employees who work at SPMI units of Private Universities in West Sumatra, amounting to 241 people. Of the 241 people taken 30 as a sample of validity and reliability so the remaining 211 people still exist. While the number of samples taken using the saturation sampling technique, which is a sampling technique by taking the entire population that is 211 samples. The approach in this study uses a quantitative approach to the survey method and uses Partial Least Square (PLS) data analysis. But before the analysis, the outer model test is first performed through the validity and reliability test. The next step is to test the Inner Model through the R-Square (Coefficient of determination), F-Square (f2 effect size), and Q-Square (Predictive Relevance) tests. The results showed that perceived organizational support and competence had a positive and significant effect on organizational citizenship behavior (OCB) and performance, as well as OCB had a positive and significant effect on employee performance at SPMI Private University in West Sumatra.